The Impact of Online Learning During the Covid-19 Pandemic on Citizenship Education Courses in Improving the Nationality Insights of Siliwangi University Students - Kosasih Adi Saputra (Jurnal Citizenship: Media Publikasi Pendidikan Pancasila dan Kewarganegaraan, 2022)
The biggest challenge in learning Citizenship Education during the COVID-19 pandemic is achieving the goals of character development and indoctrination of national insight. This article conveys the formulation of how the impact of online learning during the covid-19 pandemic on Citizenship Education courses in improving the Nationality Insights of Siliwangi University Students? This research is a survey using a quantitative-descriptive approach. Respondents were Siliwangi University students in the even semester of the 2020/2021 academic year who contracted Citizenship Education courses. The research time starts from May 2021 to December 2021. The results show that the impact of the COVID-19 pandemic on Citizenship Education courses is at a satisfaction level of 85.07%. There are limitations of students in understanding the lecture material. However, all of that can be overcome by mutual understanding between student lecturers regarding techniques, time, and learning media. Lecturers try to design learning through various improvisations, use of media and innovations as well as learning techniques. Meanwhile, the increase in the national insight of Siliwangi University students is at a satisfaction level of 83.49%. Although there are still many shortcomings. However, the lecturers have tried their best to convince and provide the best to achieve the learning objectives Citizenship Education through various learning media to increase students' national insight